Multi-channel electroluminescence of CdTe/CdS core-shell quantum dots implemented into a QLED device. (March 2019) - Pidluzhna, А.; Ivaniuk, K.; Stakhira, P.; Hotra, Z.; Chapran, M.; Ulanski, J.; Tynkevych, O.; Khalavka, Y.; Baryshnikov, G.V.; Minaev, B.F.; Ågren, H.
Abstract: CdTe/CdS core-shell quantum dots were synthesized and implemented into a light emitting device resulting in multi-channel electroluminescence with a light-green emission color. The main electroluminescence band at about 530 nm corresponds to the emission by the CdTe core (type I core/shell structure), while the next emission band at 595 nm is assigned to the crossed recombination of electrons from the conduction band of the CdS shell and holes from the valence band of the CdTe core (type II core/shell structure). At the same time, the photoluminescence spectrum of the synthesized CdTe/CdS core-shell quantum dots contains only one emission band distinctive for type II structures. This behavior of CdTe/CdS core-shell quantum dots upon the electroexcitation allows the extension of the electroluminescence spectrum in the optical region in a way that is useful for lighting-source applications. Such multi-channel electroluminescence can most probably also be reproduced in related core-shell systems accounting for size-confinement between the core size and shell thickness. Graphical abstract: Highlights: The CdTe/CdS core-shell quantum dots based QLED was fabricated. This QLED demonstrates multi-channel electroluminescence. The quantum dots demonstrate the mixed electroluminescence typical for type I and type II core-shell systems. The strain-induced band shift effect was observed for the 1 s -1 s transition in CdTe core in the presence of CdS shell.